Attribute-based key-insulated signcryption with bidirectional anonymity - Xing-lan ZHANG; Zhen ZHANG (Tongxin xuebao)
To solve exposure of secret key in attribute-based signcryption with anonymity for both sender and receiver, key-insulation mechanism to attribute-based signcryption was untroduced.Given the formal definition and security no-tions,the scheme of attribute-based key-insulated signcryption was proposed,which is provably secure under the random oracle model.The improved scheme not only satisfies the requirement of bidirectional anonymity,but also achieves for-ward security and afterward security,consequently reduced the hazard of key exposure.Finally, confidentiality, authenti-cation and anonymity in attribute-based key-insulated signcryption scheme were proved based on given security notions.